2018
DOI: 10.1186/s40560-018-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of abnormal carbon dioxide levels with poor neurological outcomes in aneurysmal subarachnoid hemorrhage: a retrospective observational study

Abstract: BackgroundIn patients with aneurysmal subarachnoid hemorrhage (SAH), an association between hypocapnia and poor clinical outcomes has been reported. However, the optimal arterial carbon dioxide tension (PaCO2) remains unknown. The present retrospective study aimed to examine the association of abnormal PaCO2 levels with neurological outcomes and investigate the optimal target PaCO2 level in patients with SAH.MethodsWe retrospectively selected consecutive adult patients hospitalized in the intensive care unit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…A selection bias has been introduced by including ventilated patients only. The rate of patients with a mRS scale score of 5 and 6 is higher compared to other studies [19,36]. Only 11.3% of the patients had a favorable outcome while other publications could demonstrate a good clinical outcome with mRS < 3 in 59.5% [3].…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…A selection bias has been introduced by including ventilated patients only. The rate of patients with a mRS scale score of 5 and 6 is higher compared to other studies [19,36]. Only 11.3% of the patients had a favorable outcome while other publications could demonstrate a good clinical outcome with mRS < 3 in 59.5% [3].…”
Section: Discussionmentioning
confidence: 57%
“…These mechanisms are not closely linked to systemic P a O 2 and P a CO 2 which might explain our results. Keeping in mind that our P a CO 2 values were mainly in the normal range, a different study showed that the maximum P a CO 2 values were significantly different comparing patients with and without DCI [19]. We do not have data on microcirculation in our study, consequently the occurrence of a reversed Robin-Hood-phenomenon in SAH patients currently remains a hypothesis, which needs to be confirmed in future trials.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations